2018
DOI: 10.1159/000494216
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effect of Rifaximin with and without Lactulose on the Active Bacterial Assemblages in the Proximal Small Bowel and Faeces in Patients with Minimal Hepatic Encephalopathy

Abstract: Background: Gut microbiota play an essential role in the pathogenesis of hepatic encephalopathy (HE). Treatment strategies are directed to modulate intestinal microbiota profiles and their function by the administration of the non-absorbable disaccharide lactulose and the non-absorbable antibiotic rifaximin, which are required for long terms, but little is known on their long-term effect on gut microbiota composition and function. Aim: To characterize the active bacterial assemblages in duodenum and faeces in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…We were interested in the effect of lactulose on the cirrhotic microbiome, since available data are conflicting, showing no major alterations of the faecal microbiome between lactulose user and non-user, but withdrawal of lactulose leads to the loss of beneficial species. 16,50,51 In our cohort only 11% of the cirrhotic patients used lactulose. On univariate analysis we found that lactulose had a weak, but significant, effect on microbiome composition, which did not remain significant in multivariate analysis.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…We were interested in the effect of lactulose on the cirrhotic microbiome, since available data are conflicting, showing no major alterations of the faecal microbiome between lactulose user and non-user, but withdrawal of lactulose leads to the loss of beneficial species. 16,50,51 In our cohort only 11% of the cirrhotic patients used lactulose. On univariate analysis we found that lactulose had a weak, but significant, effect on microbiome composition, which did not remain significant in multivariate analysis.…”
Section: Discussionmentioning
confidence: 75%
“…However, in our cohort, other drugs influenced microbiome composition to a lesser extent. We were interested in the effect of lactulose on the cirrhotic microbiome, since available data are conflicting, showing no major alterations of the faecal microbiome between lactulose user and non‐user, but withdrawal of lactulose leads to the loss of beneficial species . In our cohort only 11% of the cirrhotic patients used lactulose.…”
Section: Discussionmentioning
confidence: 99%
“…87,88 However, several small studies in patients with minimal HE suggest that rifaximin exerts little influence on microbial community composition. 85,[89][90][91] Since these studies used 16S rRNA amplicon sequencing methods, the effect of rifaximin on changes to subtaxa like species or strains may have been missed. Some effects from microbiome therapies are species and even strain specific.…”
Section: Microbe-targeted Therapy: Decrease Potentially Harmful Taxamentioning
confidence: 99%
“…However, the preventive effects of rifaximin on sarcopenia incidence or progression in LC patients remain unclear. Table 2 demonstrates randomized controlled trials (RCTs) published since 2010 regarding the effects of rifaximin on outcomes in patients with decompensated LC [ 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 ]. RCTs with the improvement of sarcopenia as a primary endpoint are not found.…”
Section: Antibiotics Dysbiosis Ammonia-lowering Strategies and mentioning
confidence: 99%